A new syndrome of cleft palate associated with coloboma, hypospadias, deafness, short stature, and radial synostosis. Issue 1 (February 1977) - Abruzzo, M A; Erickson, R P
Abstract : A new syndrome characterized by cleft palate, coloboma, hypospadias, deafness, short stature, and radial synostosis has been described. The family history suggests either an autosomal dominant mode of inheritance with limited expression in females or X-linkage. Other syndromes with similar phenotypes and modes of inheritance are discussed. The need for accurate and complete family histories in cases involving cleft palate and cleft lip/palate is discussed in relation to genetic counselling and recurrent risk estimates.